2017
DOI: 10.1007/s40888-017-0084-0
|View full text |Cite
|
Sign up to set email alerts
|

The Italian economic stagnation in a Kaldorian theoretical perspective

Abstract: This paper analyses the Italian economic stagnation in a Kaldorian framework. On the theoretical ground we propose an interpretation of the Italian economic stagnation based on the continuous reduction of aggregate demand and labour productivity. We also consider the role of the banking sector as a factor driving aggregate demand and, in turn, labour productivity. We estimate a VAR for the period 2002–2015 to analyse jointly the evolution of private consumption, real GDP, private investments, credit supply, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…To address this cumulative causation issue, some authors have suggested to use vector autoregression (VAR) models, in which all variables are treated as endogenous and interdependent (e.g. Coad et al 2011, Forges-Davanzati et al 2016. We opted for a VAR model with 8 lags (two years) and a sample size of 560 observations.…”
Section: A Panel Var Modelmentioning
confidence: 99%
“…To address this cumulative causation issue, some authors have suggested to use vector autoregression (VAR) models, in which all variables are treated as endogenous and interdependent (e.g. Coad et al 2011, Forges-Davanzati et al 2016. We opted for a VAR model with 8 lags (two years) and a sample size of 560 observations.…”
Section: A Panel Var Modelmentioning
confidence: 99%
“…A search in the Web of Science All Databases (Web of Science, 2019) and Scopus (Scopus, 2019) databases reveals that the Kaldor law is considered in several regional analysis, however a limited number of references were found for Portugal and Spain. Around the world, the Kaldor developments have been considered, for instance, for the Sub-Saharan African countries (Ssozi & Bbaale, 2019), Italy (Davanzati, Patalano, & Traficante, 2019), Mexico (Reyes, 2019), Portugal (Martinho, 2019), Asian and Latin American countries (Di Meglio, Gallego, Maroto, & Savona, 2018), Saudi Arabia (Almosabbeh & Almoree, 2018), Brazil (Nassif, Feijo, & Araujo, 2018) and China (McCombie, Spreafico, & Xu, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Si el producto y la productividad del trabajo manufacturero se expanden, crecerán también las compras de insumos no manufactureros y, por tanto, de la producción no manufacturera. A su vez, la expansión de los sectores no manufactureros causará el crecimiento de la demanda por insumos manufactureros y, por tanto, de su producto, a partir de la submatriz A 12 . Esto último puede ser causa de una nueva ola de crecimiento del producto y la productividad de los sectores manufactureros.…”
Section: La Ley De Kaldor-verdoorn En Su Forma Multisectorialunclassified